Management Strategy Hospital Medical Record Using Quantitative Strategic Planning Matrix (QSPM) (Case Study at Bhayangkara Hospital, Denpasar Bali) - Annesia Malantiyaz; Muhardi Muhardi; Handri Handri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
As one of the largest hospitals in Denpasar - Bali, Bayangkara Hospital Denpasar Bali should own a special strategy to face the competition in the field of health care. One way to maintain competitiveness, both in attracting the attention of potential patient and retaining existing patients is by having a proper uunderstanding and analysis of the factors behind the management of medical records. Primary data sources were obtained from the questionnaire input, in-depth interviews and by observing data analysis using internal-external matrix, SWOT analysis and Quantitative Strategic Planning Matrix (QSPM). Medical record management at Bhayangkara Hospital Denpasar - Bali have yet to reach its maximum potential. Electronic medical records (EMR) has seen some early usage but there are several problems in its implementation and development. The Total IFE score of 2.482 which situated below 2.5 visualize the weak internal position of RSBD's medical record management, given that the institution has yet to fully utilize its strength to overcome its weakness. This indicates that the internal management of medical records was ineffective. The total EFE score reached 3.122. which scored above 2.50, indicates an effective external management of RSBD's medical records, because it has a strategy that can take advantage of the opportunities and minimize threats/negative external influences. RSBD fell in the category of cell II that prioritize growth and development (grow and build).  The strategy with the highest implementation priority is the establishment of a medical record team equipped with dedicated programmers, with the highest attraction value strategies at 7.08.